Margin Pemasaran Kopra Di Desa Wineru Kecamatan Kakas Kabupaten Minahasa - Tiwouw, Regina Esra; Jocom, Sherly Gladys; Timban, Jean Fanny Juanita (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2025)
This study aims to analyze copra marketing margins in Wineru Village, Kakas District, Minahasa Regency. This research was carried out for 3 months from September to November 2023 from preparation to preparation of research reports. The data used is primary data. Primary data was obtained from direct interviews with farmers and copra marketing institutions using a list of questions as a tool in data collection. Based on the results of research and discussion that copra marketing in Wineru Village, Kakas District, Minahasa Regency there is only one channel, namely Farmers - Collecting Traders - Factories with the number of collecting traders 2 people is a one-level type with the amount of profit margin on Collecting Traders I am IDR 713.27/kg and on Collecting Traders II with a profit margin of IDR 601.43/kg.